MARYAM IN THE HOLY QUR'AN: Maryam In The Holy Qur'an - Fajrika, Alifa; Buchari M; Onrico Candra; Abdul Qadir Annafati (Nida Al-Qur'an: Jurnal Pengkajian Islam, 2025)
This research examines the narrative of Maryam in the Holy Qur’an analyzes key dimensions of her story, including divine favor, the tests she endured, and the miraculous birth of Isa (peace be upon him). Drawing upon classical interpretations and modern scholarly insights, this research demonstrates how Maryam’s story embodies faith, purity, and sacrifice. It also highlights her exceptional status as chosen above the women of all worlds, offering enduring moral and spiritual lessons relevant to contemporary readers. It using a thematic exegesis method (tafsir maudhu’i). The primary sources referenced are the Qur’an and additional sources include books that provide further information and support this research, such as At-Tafs?r al-Kab?r by Fakhruddin ar-Razi, Tafs?r al-Qur’?n al-‘A??m, by Ibn Kathir, Tafs?r al-Qurtub? by Qurtubi, and other relevant works. The analysis explores the story of Maryam (Mary) as presented in the Holy Qur’an, focusing on the divine favor she received, the unique trials she endured, and the spiritual lessons derived from her life. This study discusses Maryam’s special status granted by God, including her early dedication to the service of Bayt al-Maqdis, her miraculous provision, and her selection above all other women. Furthermore, it examines the challenges she faced: receiving the news of giving birth to a prophet without a father, enduring accusations from her people, and her solitude during childbirth. The research highlights the significance of parental piety, steadfast faith, and trust in divine decree as central lessons from Maryam’s story. In conclusion, Maryam’s narrative in the Qur’an is presented not only as a historical account but as an enduring moral and spiritual guide emphasizing purity, patience, and complete reliance on God.